Primary retroperitoneal hydatid cyst: a rare case with atypical presentation - Pratap, Vishnu; Ayyar, Pallavi; Prabhakar, S. (International Surgery Journal, 2018)
Primary Retroperitoneal Hydatid Cyst is a rare presentation of a disease caused by Echinococcus granulosus. Any organ of the body could be affected by the disease, although there are only a limited number of cases where the primary lesion is in the retroperitoneum. A definitive diagnosis requires a combination of imaging, serologic and immunologic tests. Ultrasonography, computed tomography and magnetic resonance imaging are highly accurate in detecting a hydatid cyst. Diagnosis of retroperitoneal hydatid cysts remain difficult as the clinical and laboratory findings are usually nonspecific. We report a case of a 47-year-old male who had an incidental finding of a retroperitoneal mass behind the left kidney. The CT scan of abdomen was suggestive of Retroperitoneal Hydatid Cyst. Patient underwent marsupialisation of cyst. Histopathological Report was suggestive of Hydatid Cyst.